Cryptogenic stroke and seronegative antiphospholipid syndrome: a case series of patients with positivity for "non-criteria" antiphospholipid antibodies - S. Mancuso; M. De Michele; S. Truglia; A. Capozzi; L. Rapino; I. Berto; C. Alessandri; D. Toni; V. Manganelli; M. Sorice; F. Conti (PAGEPress Publications, 2024)
Cerebrovascular events (CE) are one of the most common and severe events in antiphospholipid syndrome (APS), a condition characterized by thrombosis and circulating anti-phospholipid antibodies (aPL). Seronegative APS (SN-APS) refers to a group of patients with clinical features of APS but persistently negative tests for "criteria aPL": anti-cardiolipin antibodies (aCL) and anti-β2glycoprotein I antibodies detected by enzyme-linked immunosorbent assay (ELISA), and the lupus anticoagulant detected by clotting assays. We report a series of five cases of SN-APS in young or middle-aged patients who tested positive for "non-criteria" aPL. We retrospectively collected cases of SN-APS patients who experienced CE without an identified cause despite an extensive diagnostic work-up and tested negative for criteria aPL. All the patient sera were tested for aCL by immunostaining on thin-layer chromatography (TLC) and anti-vimentin/cardiolipin (aCL/Vim) by ELISA. We identified five cases of female patients aged 21 to 58 years, evaluated at the Rheumatology Unit and/or Stroke Unit/Emergency Department of the Sapienza University Hospital of Rome, "Policlinico Umberto I". All patients presented a clinical history suggestive of APS. All the patients tested positive for aCL by TLC-immunostaining, and one patient was positive for aCL/Vim. In young or middle-aged patients with cryptogenic CE and a clinical history suggestive of APS, the use of new diagnostic tools for identifying aPL, if validated in future studies, could represent an important step in the prompt diagnosis of APS.